2003
DOI: 10.1021/jp034733s
|View full text |Cite
|
Sign up to set email alerts
|

Decay Pathways of Thymine and Methyl-Substituted Uracil and Thymine in the Gas Phase

Abstract: We report observations of a dark state in the decay pathways of thymine, 1,3-dimethyl thymine, 1,3-dimethyl uracil, and 1-methyl uracil in the gas phase. After initial excitation by a nanosecond laser, the excited molecules failed to return to the ground state but rather were trapped in a dark state for tens to hundreds of nanoseconds. This result contradicts those reported in water solutions. We therefore propose that the photochemistry of these pyrimidine bases is different in the gas phase from that in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
156
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(172 citation statements)
references
References 31 publications
15
156
0
1
Order By: Relevance
“…Reported lifetimes from photoelectron measurements for the 1 n * state are on the order of several hundred femtoseconds to several picoseconds for all of the pyrimidines (29,42,43). In contrast to these reports, Kong and coworkers (45,46) detected a state with a many-nanosecond lifetime upon electronic excitation of isolated Thy and Ura. They assigned this state to a 1 n * state, which they suggested would be undetectable in solution (46).…”
Section: Discussionmentioning
confidence: 92%
“…Reported lifetimes from photoelectron measurements for the 1 n * state are on the order of several hundred femtoseconds to several picoseconds for all of the pyrimidines (29,42,43). In contrast to these reports, Kong and coworkers (45,46) detected a state with a many-nanosecond lifetime upon electronic excitation of isolated Thy and Ura. They assigned this state to a 1 n * state, which they suggested would be undetectable in solution (46).…”
Section: Discussionmentioning
confidence: 92%
“…3,4,17 He et al 10,18 observed access to long-lived (23-209 ns) dark states of thymine, methylated thymine, and methylated uracil, as well as a general tendency for longer lifetimes at lower excitation wavelengths (approx. range 290-220 nm) and higher degree of methyl substitution (up to two sites).…”
Section: A Non-dissociative Mpi Of Isolated Uracilmentioning
confidence: 99%
“…This entire deactivation mechanism still proceeds on a pico-second timescale. However, an additional sub-nanosecond to nanosecond relaxation pathway to a nonfluorescent ("dark") state has been reported in many experimental studies 1,27,28 . This state was also observed for methylated derivatives of uracil and thymine 29,30 .…”
Section: Introductionmentioning
confidence: 99%
“…This state was also observed for methylated derivatives of uracil and thymine 29,30 . Several candidates for the dark state have been suggested, including the vibrationally "hot" ground state, the S 1 state of 1 (nπ*) character, and the T 1 state of 3 (ππ*) or 3 (nπ*) character [27][28][29][30][31][32][33] . The involvement of different tautomeric forms of thymine was ruled out by Schultz and co-workers on the basis of theoretical calculations 28 .…”
Section: Introductionmentioning
confidence: 99%